2019
DOI: 10.1111/chd.12707
|View full text |Cite
|
Sign up to set email alerts
|

Blalock-Taussig shunt versus patent ductus arteriosus stent as first palliation for ductal-dependent pulmonary circulation lesions: A review of the literature

Abstract: Background Infants with ductal‐dependent pulmonary blood flow (PBF) often undergo a palliative procedure to provide a stable source of PBF prior to definitive palliation or repair. In the current era, a surgical shunt or ductal stent is used to provide PBF. We aimed to review the current literature comparing ductal stents to surgical shunts. Methods and Results Four small, single‐center studies and two larger multicenter studies were identified comparing ductal stent to surgical shunt. Combined, these studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 20 publications
(22 reference statements)
2
22
0
Order By: Relevance
“…As for pulmonary artery growth, a number of studies have examined that and have showed either equivalent or superior and more symmetrical growth of the branch pulmonary arteries following DS compared to mBTS. [7][8][9] This new study from Duke University is definitely in line with the findings from previously published reports.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…As for pulmonary artery growth, a number of studies have examined that and have showed either equivalent or superior and more symmetrical growth of the branch pulmonary arteries following DS compared to mBTS. [7][8][9] This new study from Duke University is definitely in line with the findings from previously published reports.…”
supporting
confidence: 91%
“…In the past decade, there have been a number of single-center and multi-institutional reports that compared outcomes between infants who received mBTS versus DS, and they showed that DS were associated with either equivalent or superior outcomes. [6][7][8] Overall, it seems that patients who receive DS may be expected to recover faster than those who receive mBTS, to require shorter mechanical ventilation, intensive care unit or hospital stay durations, and to have lower complications including cardiac arrest or ECMO need. Additionally, some of these reports have shown decreased early intervention with DS compared to mBTS, and some have shown decreased procedure mortality and improved overall survival toward subsequent planned operation with DS compared to mBTS.…”
mentioning
confidence: 99%
“…Use of the ductal curvature index to assess the risk of ductal stenting in patients with duct-dependent pulmonary circulation patients the need for thoracotomy and reduce postoperative complications as well as asymmetrical development of pulmonary arteries. Additionally, it reduces the mortality rate and the need for extracorporeal membrane oxygenation (ECMO) (9)(10)(11)(12)(13). Despite the new developments in the field of coronary stents and the introduction of drug eluting stents that minimise in-stent stenosis and prolong the stent patency (12,14), stenting of ducts with increased tortuosity ,especially when associated with pulmonary stenosis, is still challenging and fraught with risks (15)(16)(17).…”
Section: Original Articlementioning
confidence: 99%
“…Reports of refractory cardiac arrest following shunt insertion have even been described 27 . Ductal stenting is a reasonable alternative to the MBTS, as it is associated with similar or improved pulmonary artery growth, fewer complications, a shorter length of stay, and improved survival 30 …”
Section: Managementmentioning
confidence: 99%